The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12916-021-02045-x
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and child mental health: an electronic birth cohort study

Abstract: Background Adverse childhood experiences (ACEs) are negatively associated with a range of child health outcomes. In this study, we explored associations between five individual ACEs and child mental health diagnoses or symptoms. ACEs included living with someone who had an alcohol-related problem, common mental health disorder or serious mental illness, or experienced victimisation or death of a household member. Methods We analysed data from a pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 70 publications
1
12
0
Order By: Relevance
“…In the present study, about half of the children were exposed to a considerable number of ACEs (3 or more), with increased prevalence proportional to increased age (children over two years old). In agreement, other studies that followed children also observed a rise in ACEs concomitant to the aging of children 21 , resulting in older children resorting to more coping strategies with ACEs 22 .…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, about half of the children were exposed to a considerable number of ACEs (3 or more), with increased prevalence proportional to increased age (children over two years old). In agreement, other studies that followed children also observed a rise in ACEs concomitant to the aging of children 21 , resulting in older children resorting to more coping strategies with ACEs 22 .…”
Section: Discussionsupporting
confidence: 86%
“…Prior studies have also found children with chronic illness may not experience difficulties with their life satisfaction and happiness (14) . Childhood adversity also has an impact on their mental health ( 15,16 ). Our current sample includes many families from higher-income families who may already have increased support for identified adversities like comorbid medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Different forms of CAN have been widely documented as significant predictors of internalizing (such as depression and anxiety) and externalizing (such as antisocial and aggressive behavior, risky sexual behavior) problems in adulthood (Boduszek et al , 2012; Debowska and Boduszek, 2017; Filkin et al , 2022; Gardner et al , 2019; Hildyard and Wolfe, 2002; Norman et al , 2012). However, while numerous studies show the detrimental effects of CAN on mental health in adulthood, far fewer studies examine these effects in childhood and adolescence (Elmore and Crouch, 2020; Lowthian et al , 2021; Priebe and Svedin, 2008; Sharratt et al , 2023). Studies conducted to date demonstrate that child maltreatment has an adverse effect on youths’ internalizing and externalizing symptoms and disorders (Bolger and Patterson, 2001; English et al , 2005; Kukoyi et al , 2010; Li and Godinet, 2014; Oshri et al , 2011; Thornton et al , 2023).…”
Section: Introductionmentioning
confidence: 99%